2021
DOI: 10.1016/j.jpain.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Injectable PLGA-Coated Ropivacaine Produces A Long-Lasting Analgesic Effect on Incisional Pain and Neuropathic Pain

Abstract: The management of persistent postsurgical pain and neuropathic pain remains a challenge in the clinic. Local anesthetics have been widely used as simple and effective treatment for these 2 disorders, but the duration of their analgesic effect is short. We here reported a new poly lactic-co-glycolic acid (PLGA)-coated ropivacaine that was continuously released in vitro for at least 6 days. Perisciatic nerve injection of the PLGA-coated ropivacaine attenuated paw incision-induced mechanical allodynia and heat hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Tissue images indicated that there was no AA3-DLin LNP induced inflammation detected after comparison with PBS control groups (Figure S8 and S9). …”
Section: Resultsmentioning
confidence: 99%
“…Tissue images indicated that there was no AA3-DLin LNP induced inflammation detected after comparison with PBS control groups (Figure S8 and S9). …”
Section: Resultsmentioning
confidence: 99%
“…One of the main advantages of the PLGA NP delivery vector is the sustained release of encapsulated payload, which is usually governed by diffusion and degradation processes. [ 17 , 24 , 29 , 30 ] The cumulative release profiles of both plasmid and mRNA using PNP/C12‐PBAE NPs indeed showed sustained release behavior compared and reached a peak of up to 96% gene released over 8 days after a quick release within the first 24 h (Figure 3G,H ). These results clearly indicate that the PNP/C12‐PBAE NP displays a prolonged gene release behavior for both plasmid DNA and mRNA compared with C12‐PBAE formulations which have no PLGA‐PEG polymeric vector.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the histopathology and immunofluorescence assays of the proinflammatory biomarker IL‐6 in muscle tissues surrounding the PNP injection site were evaluated after 5 days post‐injection and the results showed no observable PNP nanoparticle‐mediated inflammation when compared with the control PBS injected group (Figures S6 and S7 , Supporting Information). [ 29 , 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that CS-GP hydrogel and CS-GP/PC polymeric hydrogel have excellent encapsulation efficiencies (EE) and drug loading (DL) mainly due to their porous structures and numerous functional groups (Tian et al., 2021 ). The EE and DL values of the fabricated CS-GP hydrogel and CS-GP/PC polymeric hydrogel were calculated, and the results obtained were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%